Survival Benefit of Surgical Treatment Added Into Systemic Treatment for Isolated Breast Cancer Liver Metastases: A Systematic Review and Meta-Analysis - Sun, Ming-Shuai; Liu, Hong-Jin; Yun, Yong-Yang; Yu, Zheng-Heng; Yang, Fan; Liu, Yin-Hua; Xu, Ling (Frontiers in Surgery, 2021)
Background: Compared with systemic treatment alone, whether surgical treatment combined with systemic treatment can improve survival outcomes of patients with isolated breast cancer liver metastases (BCLM) is still controversial. This meta-analysis was designed to evaluate the efficacy of surgical treatment for patients with isolated BCLM. Methods: A systematic search of PubMed, Embase, and Cochrane Library up to May 13, 2021 was conducted for relevant studies. The primary outcome was overall survival. The meta-analysis was performed using R software. The quality of the pooled study was assessed using the Newcastle-Ottawa scale. The publication bias was evaluated by funnel plots and Begg’s and Egger’s tests. Fixed- and random-effects models were applied according to heterogeneity. Results: 9 retrospective studies involving 13 cohorts (7 unmatched cohorts and 6 matched cohorts) were included in this study. The surgical cohorts had better overall survival than the systemic cohorts in the pooled analysis of all the included studies, in the subgroup analysis of liver resection, and in the subset of the matched cohorts. Conclusions: Compared with systemic treatment alone, surgical treatment combined with systemic treatment was proven to be associated with superior survival outcomes, which should be considered in selected patients with isolated BCLM.